(untitled) (Pulse, 2016)
Introduction: Cerebellopontine angle tumors are a surgical challenge to many neurosurgeons who want to operate in this space. Although most of these tumors are benign, they are a challenge because of the complex anatomy and important neurovascular structures that traverse this space. Most common cerebellopontine angle tumor is vestibular schwannoma. The management of these cases is essentially surgical. There has been a change in the surgical strategy over the years from simple intratumoral decompression to complete microsurgical excision, to radical excision with facial nerve and hearing preservation. Objectives: To study the clinical and radiological characteristics, know the pathological types and determine the surgical resectability and outcome of cerebellopontine angle tumor. Materials and Methods: It is a retrospective study done in the department of Neurosurgery, Apollo Hospitals Dhaka. 34 patients diagnosed with cerebellopontine angle tumor were recruited into the study. Results: Among 34 cases of cerebellopontine angle tumors vestibular schwannoma alone constituted 79%. Most of the tumors were large or giant tumors. Total resection was done in 25% of vestibular schwannoma and 50% of meningiomas. Anatomical preservation of facial nerve was achieved in 73% of patients. Facial nerve function as measured by the House Brackmann system. Postoperatively 61% had a score of 1 or 2; 29% had a score of 3 or 4; and 8% had a score of 5 or 6. Other complications included 2 cases of CSF leak, 3 cases of meningitis, 2 cases of lower cranial nerve palsy and 1 patient died. Conclusion: Cerebellopontine angle tumors show high incidence from 3rd to 5th decade with common symptoms being hearing loss and ataxia. Most of the patients presented at a delayed stage with large to giant tumors with no useful hearing. Sub total excision with keeping anterior part of tumor for preserving facial nerve function is the goal. Pulse Vol.8 January-December 2015 p.8-14